Our obligations to nature: interview with Holmes Rolston III - Smith, Stacey Vanek, author; Christian Science Publishing Society, publisher (Colorado State University. Libraries, 2003)
Rolston recalls memorable experiences developing his ideas on the intrinsic value of nature. Preserving animals and plants as part of God's creation. His Shenandoah Valley childhood. Struggles in nature, a cruciform creation. Watching a lioness kill a zebra as a religious experience. Rolston a cautious optimist. Wilderness areas and endangered species preserved amidst threats of global warming.
Entire interview is available at: http://www.csmonitor.com/2003/0320/p16s01-lire.html.
Keywords: Templeton Prize; Colorado State University; philosophy professor; Rolston, Holmes, 1932-2025